Psychometric Testing of Two Chinese-Version Scales on Attitudes Toward and Caregiving Behaviors for End-of-Life Patients and Families. (November 2018) - Yang, Luke; Liu, Yung-Fang; Sun, Huey-Fang; Chiang, Hsien-Hsien; Tsai, Yu-Lun; Liaw, Jen-Jiuan
The study purpose was to examine the validities and reliabilities of the Chinese-versions Frommelt Attitudes Toward Care of the Dying Scale (Attitudes Scale) and Caregiving Behaviors Scale for End-of-Life Patients and Families (Behaviors Scale). The scales were tested in a convenience sample of 318 nurses with ≥6 months work experience at three hospitals. Cronbach's alphas of the Attitudes and Behaviors Scales were .90 and .96, respectively. Each scale had Kaiser–Meyer–Olkin index >.85 and Bartlett's test of sphericity >4000 ( p < .001). Attitudes Scale loaded on three factors: respecting and caring for dying patients and families, avoiding care of the dying, and involving patients and families in end-of-life care. The Behaviors Scale loaded on two factors: supporting dying patients and families, and helping families cope with grief. Factor loadings for both scales were ≥.49. Both Attitudes and Behaviors Scales are reliable and valid for evaluating nurses' attitudes and caregiving behaviors for the dying.